2023
DOI: 10.1002/pon.6118
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of early‐stage breast‐cancer patients diagnosed with COVID‐19 in the first three waves of the epidemic treated in the Spanish region of Navarre

Abstract: Objectives: To describe the Quality of Life (QOL) of breast-cancer patients diagnosed with COVID-19 and analyse its evolution, compare the QOL of these patients according to the COVID-19 wave in which they were diagnosed, and examine the clinical and demographic determinants of QOL. Methods: A total of 260 patients with breast cancer (90.8% I-III stages) and COVID-19 (85% light/moderate) were included (February-September 2021) in this study. Most patients were receiving anticancer treatment (mainly hormonother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…In line with these findings in breast cancer patients, a study from the Netherlands [2] found minor differences in HRQoL measures during the early phase of the pandemic (compared to the pre-pandemic period). Another study from Spain [29] found that breast cancer patients seemed to adapt well to the COVID-19 pandemic. On the contrary, a single-center study from the USA showed that HRQoL in breast cancer patients was worsened by the COVID-pandemic (compared to the pre-pandemic period) [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings in breast cancer patients, a study from the Netherlands [2] found minor differences in HRQoL measures during the early phase of the pandemic (compared to the pre-pandemic period). Another study from Spain [29] found that breast cancer patients seemed to adapt well to the COVID-19 pandemic. On the contrary, a single-center study from the USA showed that HRQoL in breast cancer patients was worsened by the COVID-pandemic (compared to the pre-pandemic period) [30].…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of the study include the large sample size, the cancer-free control group, and data across three phases of the COVID-19 pandemic. This is in contrast to other studies of HRQoL in women with breast cancer during the pandemic which lacked a control group and post-pandemic comparison group [2,16,[28][29][30]. As mandated by law, reporting of cancer cases to the CRN ensures a complete dataset of all diagnosed breast cancer patients [36].…”
Section: Strengths and Limitationsmentioning
confidence: 97%